CP12 provides a new mode of light regulation of Calvin cycle activity in higher plants - Wedel, Norbert (The National Academy of Sciences of the USA, 1997)
CP12 is a small nuclear encoded chloroplast protein of higher plants, which was recently shown to interact with NAD(P)H–glyceraldehyde-3-phosphate dehydrogenase (GAPDH; EC 1.2.1.13), one of the key enzymes of the reductive pentosephosphate cycle (Calvin cycle). Screening of a pea cDNA library in the yeast two-hybrid system for proteins that interact with CP12, led to the identification of a second member of the Calvin cycle, phosphoribulokinase (PRK; EC 2.7.1.19), as a further specific binding partner for CP12. The exchange of cysteines for serines in CP12 demonstrate that interaction with PRK occurs at the N-terminal peptide loop of CP12. Size exclusion chromatography and immunoprecipitation assays reveal the existence of a stable 600-kDa PRK/CP12/GAPDH complex in the stroma of higher plant chloroplasts. Its stoichiometry is proposed to be of two N-terminally dimerized CP12 molecules, each carrying one PRK dimer on its N terminus and one A2B2 complex of GAPDH subunits on the C-terminal peptide loop. Incubation of the complex with NADP or NADPH, in contrast to NAD or NADH, causes its dissociation. Assays with the stromal 600-kDa fractions in the presence of the four different nicotinamide-adenine dinucleotides indicate that PRK activity depends on complex dissociation and might be further regulated by the accessible ratio of NADP/NADPH. From these results, we conclude that light regulation of the Calvin cycle in higher plants is not only via reductive activation of different proteins by the well-established ferredoxin/thioredoxin system, but in addition, by reversible dissociation of the PRK/CP12/GAPDH complex, mediated by NADP(H).